2008
DOI: 10.1016/j.intimp.2007.08.022
|View full text |Cite
|
Sign up to set email alerts
|

Assembly, activation, and physiologic influence of the plasma kallikrein/kinin system

Abstract: The plasma kallikrein/kinin system that consists of the proteins factor XII, prekallikrein, and high molecular weight kininogen was first recognized as a surface-activated coagulation system arising when blood or plasma interacts with artificial surfaces. Although surface-activated contact activation occurs in vivo when various negatively charged surfaces become exposed, including a developing platelet thrombus, a physiologic, non-injury mechanism for activation, regulation, and function of this system has bee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
66
0
9

Year Published

2009
2009
2021
2021

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 81 publications
(76 citation statements)
references
References 59 publications
1
66
0
9
Order By: Relevance
“…However, FXII activation is greatly enhanced in the presence of dextran sulfate, suggesting that negatively charged protein aggregates are better contact system-activating surfaces (13). Based upon these established facts (41) and our data (Fig. 1), we propose that the contact system is a broad pattern recognition system, recognizing negative charges rather than specific chemical structures.…”
Section: Discussionsupporting
confidence: 73%
See 1 more Smart Citation
“…However, FXII activation is greatly enhanced in the presence of dextran sulfate, suggesting that negatively charged protein aggregates are better contact system-activating surfaces (13). Based upon these established facts (41) and our data (Fig. 1), we propose that the contact system is a broad pattern recognition system, recognizing negative charges rather than specific chemical structures.…”
Section: Discussionsupporting
confidence: 73%
“…Contact System Is a Pattern Recognition System-It has been reported that in vitro contact system activation occurs on physiologically relevant surfaces such as articular cartilage, skin, sodium urate crystals, and calcium pyrophosphate (41). In vivo contact system activation occurs on developing thrombus, RNA and DNA from degrading cells, enriched polysomes from platelet membranes, ␤-amyloid, sulfatides, fatty acids, cholesterol sulfate, GAGs, activated platelet surface during platelet transfusion (42), ionic contrast media (43), and also under conditions of sepsis, where bacteria lipopolysaccharides provide a negatively charged surface (44 -47).…”
Section: Discussionmentioning
confidence: 99%
“…Chymase, chymotrypsin-like, cathepsin A, B, D, and G involvement was excluded because 100 M of the serine protease inhibitor chymostatin inhibited NPY 3-36 degradation only by 32%. We then chose the serine protease inhibitor gabexate mesylate (29,30), an antithrombotic agent able to inhibit several proteases involved in multiple proteolytic systems in plasma, including the classic complement pathway, plasmin, and kallikrein in the fibrinolytic pathway, and the activation of factor IX in the coagulation cascade (31,32). A dose-dependent inhibition of NPY production was observed with gabexate mesylate from Table 1.…”
Section: Determination Of the Kinetic Constants Of Dppiv And Amp On Nmentioning
confidence: 99%
“…FXIa generated through this loop further enhances thrombin generation, leading to a faster and more stable thrombus formation. FXIIa deficiency has been shown to be associated with a prolonged activated Partial Thromboplastin Time (aPTT), suggesting that FXII has a useful predictive value of the vascular blood flow [14]. Although FXII was considered to have a major role in the activation of the fibrinolytic pathway, recent reports indicate that its role may be limited [15].…”
Section: Introductionmentioning
confidence: 99%